2013
DOI: 10.1161/circheartfailure.112.000280
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification and Transplant Benefit in Children Listed for Heart Transplant in the United States

Abstract: Background-The sickest children among those listed for heart transplant (HT) are also at higher risk of post-transplant mortality. We hypothesized that transplant benefit, defined as percentage reduction in risk of 1-year mortality on receiving HT, increases with higher risk of wait-list mortality. Methods and Results-We analyzed all children aged <18 years listed for first HT in the United States between July 2004 and December 2010. We developed a model for 90-day wait-list mortality (or removal because of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…2 The process of HT evaluation encompasses a careful assessment of risk factors and estimating the risk of wait-list and post-transplant mortality in all candidates. 5 Our results do not support the notion of additional risk attributable to the diagnosis of myocarditis over and above that inherent in the severity of heart failure. Because our analysis is limited to children who were already listed for HT and it is unknown whether specific clinical, viral, and immunologic factors (such as duration between presentation and listing, specific viral agent identified, or active viremia) were considered before listing, how these factors contribute to post-transplant risk remains unknown.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…2 The process of HT evaluation encompasses a careful assessment of risk factors and estimating the risk of wait-list and post-transplant mortality in all candidates. 5 Our results do not support the notion of additional risk attributable to the diagnosis of myocarditis over and above that inherent in the severity of heart failure. Because our analysis is limited to children who were already listed for HT and it is unknown whether specific clinical, viral, and immunologic factors (such as duration between presentation and listing, specific viral agent identified, or active viremia) were considered before listing, how these factors contribute to post-transplant risk remains unknown.…”
Section: Discussioncontrasting
confidence: 90%
“…[13][14][15][16] Indeed, several investigators have suggested using a combination of baseline risk factors-either using a score-based tool or a more sophisticated statistical model-to risk-stratify pediatric HT recipients for early posttransplant mortality. 5,15,17,18 The specific risk factors in these models may vary somewhat but, considered broadly, include younger age or congenital heart disease (markers of surgical complexity), level of hemodynamic support at transplant (a marker of heart failure severity), and presence of end-organ [18][19][20] A common analytic approach in clinical epidemiology when evaluating new risk factors (such as myocarditis) is to adjust for known risk factors even when they are not statistically significant in the cohort analyzed so that their confounding effect is accounted for. Our results suggest that the association of myocarditis with post-transplant survival is confounded by heart failure severity at the time of HT.…”
Section: Discussionmentioning
confidence: 99%
“…14 More recently, Singh et al 77 reported an analysis of the United Network of Organ Sharing database that assessed the benefits of transplantation by evaluating the ability of heart transplantation to lower the risk of death. Their model compared mortality with and without transplantation in the first year after listing.…”
Section: Indications For Transplantation In Chd 93mentioning
confidence: 99%
“…Therefore, once clinical fluid overload is relieved, the potential benefit of more aggressive diuresis aimed at attaining normal filling pressures should be weighed carefully against the potential risk of worsening renal function in children. 19 Third, the risk of death or deterioration associated with hemodynamic profiles should be carefully considered when evaluating a child for ventricular assist device implantation. 20,21 Finally, these findings raise important questions for future research such as whether clinical evaluation correlates with intracardiac hemodynamics in children with advanced heart failure and whether hemodynamic congestion and hypoperfusion can be diagnosed clinically.…”
Section: Discussionmentioning
confidence: 99%